EMBRIOLOGI DALAM AL-QUR'AN: KAJIAN PADA PROSES PENCIPTAAN MANUSIA - Kiptiyah, Kiptiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2007)
Researchers have studied human embryology for many centuries, but there's no yet detailed appropriate explanation about the process of human creation: even the told theory sometimes digress from the fact. This caused by the limitation of human science and knowledge.Al-Qur'an explains in detailed how Allah creates human. Allah said in Surat al-Mu'minuun, verse 12-14. Man We did create from a quintessence (of clay); then We placed him as (a drop of) sperm in a place of rest, family fixed; then We made the sperm into a clot of congealed blood; then of that clot We made a (fetus) lump; then We made out of that lump bones and clothed the bones with flesh; then We developed out of it another creature. So blessed be God, the best to create! Thirteen centuries after al-Qur'an released, there were researchers on embryology. The result of those researchers proved the legitimate concepts of embryology in al-Qur'an. Based on those findings, this research's theme is: